KARAKTERISTIK MUTU KOLAGEN DARI LIMBAH PRODUKSI TUNA LOIN QUALITY CHARACTERISTIC OF COLLAGEN EXTRACTED FROM TUNA LOIN PRODUCTION WASTE - Rahantan, Mahlidah; Lalopua, Vonda Milca N; Savitri, Imelda krisanta Enda (Program Studi Pendidikan Biologi FKIP Unpatti, 2024)
Background: Frozen tuna loin industrial waste produces solid waste in the form of pieces of head, tail, fins and innards . By-products of tuna loin production produce around 15% bone, around 30% head, and around 10% remaining skin and scales . Solid waste from tuna loin production can be used as raw material for collagen production. Collagen characteristics vary according to the type of fish, fish body part, extracting material, and extraction technique . Methods: The research method was experimental by applying two collagen source treatments , namely skin waste (A1) and a combination of head, bone and tail waste (A2). Results: The results of the research show that The collagen yield value obtained from leather waste (A1) was 4.02% with a water content of 11.89%, ash 1.26%, protein 52.58% and a pH value of 3.74. Meanwhile, the yield of collagen obtained from mixed head, bone and tail waste (A2) was 1.256% with a water content (9.61%), ash 1.49%, protein 53.94% and a pH value of 3.23% . Conclusion: The water and ash content of collagen from skin waste (A1) and the combined tuna loin head, bone and tail waste (A2) meet the quality of SNI 8076:2014